1989
DOI: 10.1145/65445.65447
|View full text |Cite
|
Sign up to set email alerts
|

Virtual video editing in interactive multimedia applications

Abstract: Drawing examples from four interrelated sets of multimedia tools and applications under development at MIT, the authors examine the role of digitized video in the areas of entertainment, learning, research, and communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(41 citation statements)
references
References 4 publications
0
39
0
1
Order By: Relevance
“…A main component of interactive videos is a browsing functionality that enables a user to access a linear video in a nonlinear way. After partitioning a video into smaller segments [Mackay and Davenport 1989;Chang et al 2007], single scenes can be omitted [Chang et al 2007] or jumps to specific video parts are possible [Zhang et al 2006]. Zhang et al "allow proactive and random access to video content based on queries or search targets" [Zhang et al 2006] in interactive videos.…”
Section: Fundamentals and Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…A main component of interactive videos is a browsing functionality that enables a user to access a linear video in a nonlinear way. After partitioning a video into smaller segments [Mackay and Davenport 1989;Chang et al 2007], single scenes can be omitted [Chang et al 2007] or jumps to specific video parts are possible [Zhang et al 2006]. Zhang et al "allow proactive and random access to video content based on queries or search targets" [Zhang et al 2006] in interactive videos.…”
Section: Fundamentals and Termsmentioning
confidence: 99%
“…As a result, "users can select or play a segment with minimal search time" [Zhang et al 2006]. Mackay and Davenport state that it is possible to increase the level of interactivity "by allowing users to build, annotate, and modify their own environments" [Mackay and Davenport 1989]. -Nonlinear Videos consist of a set of scenes or video sequences, which are arranged in a library or as a walk-through in a graph structure [Kozuch et al 2000].…”
Section: Fundamentals and Termsmentioning
confidence: 99%
“…For example, Mackay and Davenport examined the role of digital video in several interactive multimedia applications and concluded that video is an information stream that can be tagged, edited, analyzed, and annotated [13]. Later, Davenport et al proposed using metadata for home movie editing assistance [7].…”
Section: Metadata and Video Editingmentioning
confidence: 99%
“…For example, there is considerable interest in the psychophysiology of emotion in social interactions (Levenson & Gottman, 1983, 1985. One can readily envision a workstation that could display a video record of, say, a couple's discussion of marital problems, synchronized with a transcript of the dialogue and plots of each partner's heart rate (MacKay & Davenport, 1989). What is needed, however, is a standard means to include time markers in textual transcripts, so that the transcript can be synchronized with the other data channels.…”
Section: Multimedia Data Structuresmentioning
confidence: 99%